Risk Factors For Occurring Preeclampsia In Pregnant Women : Literature Review - Desriva, Nia; Sansuwito, Tukimin Bin; Dioso, Regidor III (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Preeclampsia is a potentially dangerous pregnancy complication characterized by high blood pressure. This condition usually occurs when the gestational age reaches 20 weeks. Preeclampsia has an impact when pregnant and giving birth also results in postpartum problems due to endothelial dysfunction in various organs. Long-term effects can also occur in babies born to mothers with preeclampsia. With the high rate of preeclampsia in Indonesia and globally, this study aims to determine the risk factors for preeclampsia in pregnant women. The form of this research is Literature Review using a journal search on Google Scholar. The keywords used are Preeclampsia; Cause; and Pregnancy. After being selected, five journals will be reviewed, four journals are cross-sectional studies and one other journal is a case control study. The conclusion of this study The risk factors for preeclampsia in pregnant women include history of hypertension, history of preeclampsia, age, Body Mask Index (BMI), parity, stress, knowledge, completeness of Antenatal care (ANC), diet and exposure to cigarette smoke.